Les mesures corporelles dans les rituels mexicains - Danièle Dehouve (Ateliers d'Anthropologie, 2014)
Indian rituals past and present attribute an important place to numeration. This article offers a comparison between the Nahua system of measurements inherited from the Conquest period and the Tlapanec system observed today. It shows that both are based on body measurements open to mutual conversion, the logic of equivalencies being of pre-Colombian origin. Ritual uses are also similar. Every ceremony included the precise counting of ceremonial objects, as well as the measurement of their dimensions. The fact of transmitting the measurements of a given individual or priest to an object, or endowing it with large or small dimensions, created specific ritual effects.